Penerapan Weekly Order Change untuk Mengurangi Waktu Pemesanan di PT Toyota Motor Manufacturing Indonesia - Kevin Alim Sompie; I Gede Agus Widyadana (Jurnal Titra, 2016)
PT Toyota Motor Manufacturing Indonesia (TMMIN) have business at export service part. This business have problem at procuring time from Toyota Astra Motor (TAM) as customer to TMMIN. Lead time for TAM order to TMMIN is 13 days while the standard procuring time is 2 days. The differences make some order status is backorder or delay. The differences caused by TMMIN procuring timing only once every month. This study give advice to using weekly order change (WOC). WOC can be applied but need to consider production capacity and raw material limit. That factor will be used for limitation at simulation. Simulation will use order date at backorder shipment and emergency order data from January until March 2016. Data will be used for simulation input with limitation at production capacity and raw material. Current lead time ordering process can be reduce until 3 days with WOC.